2020
DOI: 10.3390/nano10122529
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hollow Channels Surrounded by Gold Nanoparticles in Hydrogel by Femtosecond Laser Irradiation

Abstract: The fabrication of hollow channels surrounded by gold nanoparticles in poly(ethylene glycol) diacrylate (PEGDA) is demonstrated. The absorption spectra show that gold nanoparticles were formed at the periphery of the focus by reduction of gold ions. The microscope observation and Raman spectroscopy analyses indicate that the center of the channels were void of PEGDA, which can be attributed to the femtosecond laser-induced degradation of the hydrogel. Since both the hydrogel and gold nanoparticles are biocompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The microstructures were further tested for biocompatibility by seeding neurons on them. More recently, Takayama et al [ 47 ] reported the ablation of PEGDA hydrogels, polymerized by UV curing with Irgacure ® 2959, then soaked with gold chloride and ablated by means of a Ti:Sapphire laser ( 100 fs, 800 nm, 1 kHz, objective lens 60X, NA = 0.7). Hyaluronic acid (HA) has also been used to MPL fabricate microstructures, as in the work by Oviasnikov, Liska et al [ 48 ], where a HA photoresist was developed for MPL fabrication, leading to highly versatile, biocompatible microstructures with the possibility to be enzymatically degraded.…”
Section: Light Interaction With Soft Mattermentioning
confidence: 99%
“…The microstructures were further tested for biocompatibility by seeding neurons on them. More recently, Takayama et al [ 47 ] reported the ablation of PEGDA hydrogels, polymerized by UV curing with Irgacure ® 2959, then soaked with gold chloride and ablated by means of a Ti:Sapphire laser ( 100 fs, 800 nm, 1 kHz, objective lens 60X, NA = 0.7). Hyaluronic acid (HA) has also been used to MPL fabricate microstructures, as in the work by Oviasnikov, Liska et al [ 48 ], where a HA photoresist was developed for MPL fabrication, leading to highly versatile, biocompatible microstructures with the possibility to be enzymatically degraded.…”
Section: Light Interaction With Soft Mattermentioning
confidence: 99%
“…Izumi Takayama et al [ 8 ] reported the fabrication of hollow channels surrounded by gold nanoparticles in poly(ethylene glycol) diacrylate (PEGDA). The hollow channels and gold nanoparticles were formed in a single step of irradiating a femtosecond laser pulse in PEGDA hydrogels which contained gold ions.…”
mentioning
confidence: 99%